Determining Opioid-Sparing Efficacy of Intraoperative Esketamine After Laparoscopic Gynecological Surgery [Letter] - Chen XY; Guo YH; Xue FS (Drug Design, Development and Therapy)
Xiao-Ying Chen, Yan-Hua Guo, Fu-Shan Xue Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fuzhou University Affiliated Provincial Hospital, Fujian Provincial Hospital, Fuzhou, People’s Republic of ChinaCorrespondence: Fu-Shan Xue, Department of Anesthesiology, Shengli Clinical Medical College of Fujian Medical University, Fuzhou University Affiliated Provincial Hospital, Fujian Provincial Hospital, No. 134 Dongjie, Fuzhou, 350001, People’s Republic of China, Tel +86-13911177655, Fax +86-0591-88217841, Email fushanxue@outlook.com; xuefushan@mail.ccmu.edu.cn